THE STUDY OF WHO’S THEORY TO NUMBER OF POSYANDU TARAP VISITS TO INCREASE D/S OF INFANT–TODDLERS COVERAGE - Ifroh, Riza Hayati; Susanti, Rahmi; Winanda, Wenny (Tadulako University, 2018)
Background & Objective: Maternal participation is one of the supporting factors and indispensable in monitoring the growth of infants and babies. This is reflected in the comparison of the number of children weighed with all children in the region or called the concept of D/S and involvement of parents visiting posyandu. The purpose of this study is to analyze the factors that influence the visits of mothers who have infants or toddlers to Posyandu Tarap in order to increase the number D / S through the WHO theory approach. This research is an analytic observation research with cross sectional approach. Materials and Methods: The sample that entered as the respondent in this research is the mother who recorded in data posyandu Year 2017-2018. Results: The number of visit to Posyandu Tarap on average 2 times during last 4 months. The average of respondents knowledge is 14.95 and the average of respondents attitude is 43.45. As many as 90% of respondents have family support to Posyandu Tarap. In addition, 90% of respondents were motivated to visit Posyandu Tarap to get information about infant and toddlers health, 95% of respondents considered that distance of building with Posyandu Tarap is very close. Conclusion: There is 1 causal factor from 7 research variables that influence mother visit to posyandu to weigh her baby that is mother motivation in doing visit to Posyandu Tarap.